The Effects of Achievement Motivation and Perceived Teacher Involvement in Academic Tasks on the Academic Achievement and Psychological Well-being of Rural Students in the Interior Sabah Division, Malaysia - Getrude C. Ah Gang @ Grace; Crispina Gregory K Han; Lay Yoon Fah; Lawrence Alan Bansa (2018)
This study examines the effects of achievement motivation and perceived teacher involvement on academic achievement and psychological well-being of rural students in the Interior Sabah Division (Beaufort, Keningau, Kuala Penyu, Membakut, Pensiangan, Sipitang, Tambunan & Tenom). We predicted that achievement motivation contributes to both academic achievement and psychological well-being. We also predicted teachers’ involvement in students’ academic work also contributes to both dependent variables. A total of 1586 students participated in this study from 21 rural schools in the Interior Division Sabah. A questionnaire, divided into four sections, was used to measure all the variables. Section A measured the demographic variables, such as the academic achievement, academic level, age, gender and location; Section B; measured achievement motivation; Section C measured the perception of teacher involvement in students’academic work and Section D measured psychological well-being. Hierarchical regression analyses were used to analyze the data. The study found that achievement motivation contributed 4% to the variance in academic achievement and 16% on psychological well-being. In regards to teachers’ involvement in academic studies, it contributed 6% to students’ psychological well-being but not in academic achievement. These significant findings may create awareness and bring the matter to the attention of the Ministry of Education, the schools and Parent-Teacher Association. From this study, it is our hope that the Educational Institution may provide more achievement motivational programs to enhance rural students’ psychological well-being and academic achievement.